Dynamic response of the human spine to anteroposterior mobilisation manual therapy: an interventional magnetic resonance imaging study (short communication) - McGregor,AH; Bull,AMJ; Lee,R; Wragg,P (Physiotherapy, 2004)
ObjectivesThe biomechanics of posteroanterior mobilisation (PA) is poorly understood. Studies to date have recorded static spinal kinematics but have failed to quantify the force applied during the technique. The aims of this study were to develop and validate a tool to measure the force applied to the cervical spine during the administration of PA manual therapy.Study populationNineteen control subjects (10 males, 9 females, mean age 29.1 (S.D. 6.2) years) with no history of cervical pain requiring intervention were recruited into this study and written informed consent obtained.MethodsDevice developmentThe force measurement device had to be MR compatible, give the correct feel to the examiner to simulate the normal PA manipulation technique, easy to read from within the iMR suite by the examiner, calibrated for specific levels of force application and the force values had to be recorded simultaneously with the MR images. The design of the device was fraught with complexities relating to obtaining a precise measure of force, and the magnetic environment. A simple low cost approach was used to address this problem and a fluid-filled device was constructed that could be placed between the therapists hands and the subjects neck. Synchronisation was achieved by videoing the whole test procedure and logging this video with the image sequence number and time of scanning. Although a working system was achieved the device developed was found to be limited with respect to recording absolute force and consequently the values of force recorded were lower than expected, and the extraction of force data from the videos time consuming and complex.Imaging protocolSubjects were scanned using a General Electric Signa SP10 Interventional MRI scanner (iMR) at St. Mary’s Hospital, London. This is an open MRI scanner consisting of two connected but opposing ring “doughnut” magnets. The gap between these magnets is 56 cm generating a uniform field of 0.5 T. Subjects we